Polypharmacy: Remedy Leads to Illness - Mishra, Archana; Jangir, Surbhi; Singh, Divya (Journal of Biomedical and Pharmaceutical Research, 2024)
Background: People often engage in polypharmacy, which is outlined as taking more drugs than is clinically required or using many prescriptions at one time. Objective: The goal of this research was to provide a descriptive analysis of polypharmacy and to perform the clinical assessment of the patients as well as assess their behavioural changes. Methods: A cross-sectional study was performed in tertiary care hospital over five months. A total 100 patients are included. The study population include cardiovascular and diabetic patients. Medicine card containing more than 5 medicines are included. Data collection was done by personal communication with the patients which prevents the manipulation of the information. The collected data are determined through graphical methods. Results: Polypharmacy patients were experiencing excessive behavioural changes such as anxiety and frustration. Statins and Biguanides group of medicine are prescribed more. The blood pressure and heart rate of the patients were also changing continuously due to medicines and hospital restrictions. It was found that diet and oxygen saturation level is not affected by Polypharmacy as these are continuously monitored by the hospital staffs. Conclusion: Polypharmacy frequently leads to an increased risk of medical related issues. Throughout this study, it was found that patients have major effect on their blood pressure and heart rate simultaneously which could be due to number of medicines prescribed or the hospital environment and restriction. Changes in the patient behaviour is also one of the major concerns which needs to be focused sincerely. Keywords: Polypharmacy, Blood Pressure, Heart Rate, Behaviour, Cardiovascular